Central retinal vein occlusion with cerebral infarction secondary to anlotinib treatment: a case report and literature review - Chen, Yingying; Du, Yi; Qiu, Lu; Zheng, Jing (Frontiers in Pharmacology, 2023)
Purpose: We present a rare case of an elderly man with minimal pre-existing thromboses risk, who experienced central retinal vein occlusion (CRVO) and cerebral infarction after oral intake of the anti-cancer drug anlotinib, likely due to a drug-related complication. Observations: A male, aged 65 years, sought care at the ophthalmology department because of acute painless 5-day vision loss in the right eye, in combination with cerebral infarction history, after oral intake of anlotinib for hepatocellular carcinoma (HCC) for over 16 months. Clinical assessment and ancillary examination verified a right eye central retinal vein occlusion diagnosis. Anlotinib is a multi-target tyrosine kinase inhibitors (TKIs) is reported to potently suppress vascular endothelial growth factor (VEGF) receptor, in order to exert strong antitumor angiogenesis and inhibit tumor occurrence. Although anlotinib is only regarded as a possible thrombosis risk factor, it is possible that anlotinib administration markedly enhanced vaso-occlusive risk within this patient. Conclusions and Significance: Herein, we present the first report of anlotinib-induced CRVO and cerebral infarction to our knowledge. Given our evidences, anlotinib usage is intricately linked to sight- and life-threatening thrombotic effects even among patients with reduced thrombophilic risk. Hence, patients receiving this drug must be carefully monitored for possible drug-related complications